Self-care education needs in gestational diabetes tailored to the Iranian culture: A qualitative content analysiss - Mitra Kolivand; Afsaneh Keramat; MehrAli Rahimi; Zahra Motaghi; Mohammad Shariati; MohammadHassan Emamian (Wolters Kluwer Medknow Publications, 2018)
Background: Gestational diabetes is one of the most common health problems in pregnancy that requires participation through self-care to reduce the maternal and neonatal complications. The present study aimed to determine the needs of women as an essential first step to formulate a self-care guide fitting the Iranian culture. Materials and Methods: The present qualitative study was conducted through interviews with 13 diabetic pregnant women and 10 care providers using semi-structured questionnaires in several cities of Iran in 2016. Further, the data analysis was performed using conventional content analysis. In addition, purposive sampling was performed at the diabetes clinic of Kermanshah University of Medical Sciences, Imam Reza Hospital, and health centers across Kermanshah, Shahroud, and Tehran. Results: In the present qualitative content analysis study, four themes were identified: awareness and ability (knowing diabetes, mothers training and empowerment, continuity and quality, information resources), lifestyle (healthy diet, physical activity), mental health (counseling, interaction, spirituality, and religion), and supportive family (the husband's unique role, the psychological atmosphere at home). Conclusions: The present study highlighted main aspects of self-care educational/supportive needs, specifically in the domains of lifestyle, awareness and capability, mental health, and family. The results of our analysis highlighted the needs that can be useful for developing comprehensive self-care educational programs, with a higher focus on physical activity, mental health, the role of the family, and the use of religious interests.